Get what you want : an industry insider shows you how to make good complaints, fix bad service and convince companies that you're right - Burke, Jack, 1950- (Silver Lake, 2005)
Don't accept shoddy goods or bad service! The author, who brings to his readers more than three decades of experience and consulting in the customer service field, addresses the other side of the counter the customer. He offers long-suffering consumers key tips on how to make effective complaints and how to turn problems into refunds, exchanges or improved service. Jack Burke is the president of Sound Marketing, a California-based firm that helps companies develop customer service departments, call centers and audio tools for customer service and sales support. He has held senior positions in t.